1988
DOI: 10.2190/139a-98ax-el11-d120
|View full text |Cite
|
Sign up to set email alerts
|

Risky-Choice Behavior: A Life-Span Analysis

Abstract: The purpose of the present study was to systemically test the hypothesis that older people adopt risk-avoiding strategies when faced with risky-choice situations. Ninety-six adults, representing four age cohorts, filled out a risk-taking questionnaire consisting of twelve situations demanding a choice between a safe and a risky option. One-half of the choices involved potential losses, the other half involved potential gains. The results indicated that older adults choose no more safe alternatives than do youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Volume 2-Number 1 age and risk aversion (more choices of a sure thing over a gamble) in gains-suggesting no age-related changes in the domain of gains. Holliday (1988), however, found no age differences from 20 to 76 years old in choices between gambles and sure things for gains or losses.…”
Section: Value Losses Gainsmentioning
confidence: 79%
“…Volume 2-Number 1 age and risk aversion (more choices of a sure thing over a gamble) in gains-suggesting no age-related changes in the domain of gains. Holliday (1988), however, found no age differences from 20 to 76 years old in choices between gambles and sure things for gains or losses.…”
Section: Value Losses Gainsmentioning
confidence: 79%
“…Notably, the age‐related differences reflected that younger adults did not demonstrate the framing effect—however, the effect was found among younger adults in other studies using the same stimuli 135,154 . Four other studies that compared younger and older adults indicated age similarities 133,155–157 . One of the four 157 was a replication that used the same vignettes as the study indicating age‐related differences.…”
Section: Developmental Trajectorymentioning
confidence: 92%
“…Tables 1 and 2 give an overview of the tasks and articles that investigate age‐related differences in risky choice that are included in this meta‐analysis 15–17,32 , 42–64 …”
Section: Methodsmentioning
confidence: 99%